2023
DOI: 10.1111/psyp.14465
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation attenuates neural responses to outcomes from risky decision‐making

Tianxin Mao,
Zhuo Fang,
Ya Chai
et al.

Abstract: Sleep loss impacts a broad range of brain and cognitive functions. However, how sleep deprivation affects risky decision‐making remains inconclusive. This study used functional MRI to examine the impact of one night of total sleep deprivation (TSD) on risky decision‐making behavior and the underlying brain responses in healthy adults. In this study, we analyzed data from N = 56 participants in a strictly controlled 5‐day and 4‐night in‐laboratory study using a modified Balloon Analogue Risk Task. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…[45][46][47] Sleep deficiency also impairs decision making. [48][49][50] The mechanism for disturbance of sleep architecture and its influence on decisions regarding risk for MSM in this study likely combines to produce stress and fatigue from poor sleep. Lastly, tiredness from poor sleep may make it difficult to maintain the energy needed on the job, which may limit traditional employment options and contribute to the press to engage in exchange sex.…”
Section: Discussionmentioning
confidence: 89%
“…[45][46][47] Sleep deficiency also impairs decision making. [48][49][50] The mechanism for disturbance of sleep architecture and its influence on decisions regarding risk for MSM in this study likely combines to produce stress and fatigue from poor sleep. Lastly, tiredness from poor sleep may make it difficult to maintain the energy needed on the job, which may limit traditional employment options and contribute to the press to engage in exchange sex.…”
Section: Discussionmentioning
confidence: 89%
“…18-fluorodeoxyglucose positron emission tomography in patients with Parkinson’s disease showed that increased insula, OFC, and ACC metabolism is associated with increased impulsivity scores. 25 Furthermore, human neuroimaging studies suggest that the insula, 26,27 ACC, 28,29 OFC, 28,30 and amygdala 3133 modulate their activity prior to and during risky decision making and while evaluating risk.…”
Section: Introductionmentioning
confidence: 99%